A COMPARATIVE ANALYSIS OF CONSTRAINT-HANDLING MECHANISMS FOR SOLVING ENGINEERING DESIGN PROBLEMS - GÖLCÜK, İlker (Journal of Industrial Engineering (Turkish Chamber of Mechanical Engineers), 2021)
Optimization problems have numerous real-life applications in science and engineering. The engineering design problems are usually subject to various constraints. Although many state-of-the-art metaheuristic optimization algorithms have been developed during the last decades, these algorithms require additional constraint-handling mechanisms to cope with constrained optimization problems. Therefore, selecting a suitable constraint-handling mechanism requires extensive trial-and-error experiments, which is time-consuming and demanding. In this study, a comparative analysis of the eight constraint handling mechanisms is carried out, guiding decision-makers in their optimization practices. The constraint-handling techniques are used along with the whale optimization algorithm, and 19 real-life mechanical design problems, which are also part of the CEC2020 benchmark suite, are tested in the experimental analysis. The nonparametric statistical analysis incorporating Nemenyi and Holm post-hoc procedures shows that the inverse tangent constraint-handling and eclectic penalty methods exhibit high performance in real-life mechanical design problems. Optimizasyon problemlerinin bilim ve mühendislikte çok sayıda gerçek yaşam uygulaması vardır. Mühendislik tasarım problemleri genellikle çeşitli kısıtlamalara tabidir. Son on yılda birçok modern meta-sezgisel optimizasyon algoritması geliştirilmiş olsa da bu algoritmalar, kısıtlı optimizasyon problemleriyle başa çıkmak için ek kısıt-yönetimi mekanizmaları gerektirir. Bu nedenle, uygun bir kısıt-yönetimi mekanizmasının seçilmesi, zaman alıcı ve zorlu olan kapsamlı deneme yanılma deneyleri gerektirir. Bu çalışmada, karar vericilere optimizasyon uygulamalarında yol gösterecek şekilde sekiz kısıt-yönetimi mekanizmasının karşılaştırmalı bir analizi gerçekleştirilmiştir. Kısıt-yönetimi teknikleri, balina optimizasyon algoritmasıyla birlikte kullanılmış ve deneysel analizde yine CEC2020 kıyaslama paketinin bir parçası olan 19 gerçek hayat mekanik tasarım problemi test edilmiştir. Nemenyi ve Holm post-hoc prosedürlerini içeren nonparametrik istatistiksel analiz, ters tanjant kısıt-yönetimi ve eklektik ceza yöntemlerinin gerçek hayattaki mekanik tasarım problemlerinde yüksek performans sergilediğini göstermektedir.